Provision of a local anaesthetic minor procedures service by surgical advanced clinical practitioners: 5-year study. Issue 5 (3rd September 2021) - Taib, A; Hammill, C; Abraham, A; Fakim, B; Garstang, P; Carney, J; Natarajan, V; Subar, D
Abstract: Background: Surgical advanced clinical practitioners (SACPs) form part of the extended surgical workforce drawn from a variety of allied healthcare backgrounds. The primary aim of this study was to determine whether there was a financial benefit in having minor surgical procedures undertaken by dedicated SACPs compared with operating lists assigned to consultant surgeons. Methods: This was a retrospective cohort study including all patients who had minor 'lumps and bumps' procedures undertaken between April 2014 and August 2019 at East Lancashire Hospitals NHS Trust under local anaesthetic by the general surgery team. Clinical patient information, including lesion type, was collected along with operating room staffing levels and duration of operation. The cost of the procedure was calculated as operating time multiplied by cost of staff per minute according to local banding. Results: A total of 1399 patients had a lesion excised; 907 procedures were carried out by a doctor, and the rest independently by a SACP. The majority of lesions excised were lipomas and cysts. There was no difference in the median surgical time taken between SACPs and doctors (20 (i.q.r. 14–28) min). Minor procedures carried out on consultant surgeon lists cost 62.3 per cent (€25.33) more on average than those on SACP lists (median €65.96 versus 40.63 respectively; P  < 0.001). Conclusion: A dedicated and independent SACP 'lumps and bumps' list was financially beneficial. Operating times were similar to those of doctors. These lists safely free trainee and consultant surgeons to undertake more complex work. Abstract : A dedicated and independent surgical advanced care practitioner 'lumps and bumps' list has been shown to be a financially beneficial service. Operating times are similar to those of doctors. These lists free staff for consultant lists, potentially permitting more major procedures.